Metabolism of JQ1, an inhibitor of bromodomain and extra terminal bromodomain proteins, in human and mouse liver microsomes. Issue 2 (14th April 2020) - Li, Feng; MacKenzie, Kevin R; Jain, Prashi; Santini, Conrad; Young, Damian W; Matzuk, Martin M
Abstract: JQ1 is a small-molecule inhibitor of the bromodomain and extra terminal (BET) protein family that potently inhibits the bromodomain testis-specific protein (BRDT), which is essential for spermatogenesis. JQ1 treatment produces a reversible contraceptive effect by targeting the activity of BRDT in mouse male germ cells, validating BRDT as a male contraceptive target. Although JQ1 possesses favourable physical properties, it exhibits a short half-life. Because the details of xenobiotic metabolism play important roles in the optimization of drug candidates and in determining the role of metabolism in drug efficacy, we investigated the metabolism of JQ1 in human and mouse liver microsomes. We present the first comprehensive view of JQ1 metabolism in liver microsomes, distinguishing nine JQ1 metabolites, including three monohydroxylated, one de-tert-butylated, two dihydroxylated, one monohydroxylated/dehydrogenated, one monohydroxylated-de-tert-butylated and one dihydroxylated/dehydrogenated variant of JQ1. The dominant metabolite (M1) in both human and mouse liver microsomes is monohydroxylated on the fused three-ring core. Using recombinant cytochrome P450 (CYP) enzymes, chemical inhibitors and the liver S9 fraction of Cyp3a -null mice, we identify enzymes that contribute to the formation of these metabolites. Cytochrome P450 family 3 subfamily A member 4 (CYP3A4) is the main contributor to the production of JQ1 metabolites in vitro, and the CYP3A4/5 inhibitor ketoconazole strongly inhibits JQ1 metabolism in both human and mouse liver microsomes. Our findings suggest that JQ1 half-life and efficacy might be improved in vivo by co-administration of a selective CYP inhibitor, thereby impacting the use of JQ1 as a probe for BRDT activity in spermatogenesis and as a probe or therapeutic in other systems. Abstract : Nine JQ1 metabolites were identified and characterized in liver microsomes, and the enzyme CYP3A4 mediates the formation of most JQ1 metabolites.